Long-term impacts of Legionnaires’ disease on health and wellbeing: rationale, study design and baseline findings of a matched cohort study (LongLEGIO) (Swiss Medical Weekly, 2025)
BACKGROUND AND STUDY AIMS: Is there a post-acute infection syndrome for Legionnaires’ disease? Legionnaires’ disease is a form of primarily community-acquired pneumonia caused by Legionella spp. bacteria. Legionnaires’ disease and other forms of bacterial community-acquired pneumonia may lead to persistent health and wellbeing impairments. It remains unclear whether these are caused by the community-acquired pneumonia-causing pathogen or the pneumonia itself. We present the rationale and design of a matched cohort study to investigate the persistent health impacts of Legionnaires’ disease and compare them with persistent manifestations of other bacterial (Legionella test-negative) community-acquired pneumonia. We also present baseline characteristics of the study cohorts.METHODS: Legionnaires’ disease patients and Legionella test-negative community-acquired pneumonia patients with confirmed or clinically suspected bacterial aetiology were recruited from university and cantonal/regional hospitals and matched for sex, age, hospital type and date of diagnosis. Questionnaire-based interviews are conducted at baseline and 2, 6 and 12 months after the start of appropriate antibiotics. The questionnaires focus on patient-reported outcome measures and cover long-term symptoms, use of health services and health-related quality of life.RESULTS: Between June 2023 and June 2024, 59 patients with Legionnaires’ disease (59.3% male, median age 69 years [interquartile range [IQR]: 57–80]) and 60 patients with other bacterial (Legionella test-negative) community-acquired pneumonia (63.3% male, median age 69 years [IQR: 60–79]) were enrolled. Admission to the intensive care unit was required for 13.6 % of Legionnaires’ disease patients and 8.3 % of other bacterial community-acquired pneumonia patients. Chronic kidney failure was more prevalent among Legionnaires’ disease patients (15.3% vs 10.0%), while chronic obstructive pulmonary disease (20.0% vs 11.9%), malignancies (33.3% vs 13.6%) and an immunocompromised status (25.0% vs 13.6%) were more common in Legionella test-negative community-acquired pneumonia patients. Furthermore, Legionella test-negative community-acquired pneumonia patients reported lower baseline quality of life scores than Legionnaires’ disease patients. Differences in pneumonia severity, comorbidities and self-reported quality of life scores will be accounted for in future analyses.CONCLUSIONS: The LongLEGIO study will contribute to research on post-acute infection syndromes and provide the data for a more holistic assessment of the disease burden of Legionnaires’ disease.